Edukasi Pengembangan Usaha Silvofishery dalam Kelola Ekosistem Mangrove Pada Masyarakat Desa Putri Sembilan Rupat Utara - Fauzi, Muhammad; Budijono, Budijono; Prianto, Eko; Hendrizal, Andri; Adriman, Adriman (Unri Conference Series: Community Engagement, 2024)
Silvofishery education in mangrove ecosystem management aims to integrate aquaculture with mangrove forest preservation and management, fostering a balance between human activities and environmental sustainability within mangrove ecosystems. Residents of Putri Sembilan Village, situated adjacent to the mangrove ecosystem, have the potential to enhance mangrove forest management and sustainability through silvofishery practices. This educational initiative commenced with problem identification through discussions between the community service team and the Forestry Training and Community Empowerment Unit of the Riau Provincial Environment and Forestry Service. The agreed-upon approach involved educating Putri Sembilan Rupat Utara Village residents through lectures and practical tutorials. The educational process included pre-tests, presentations, question-and-answer sessions, interactive discussions, post-tests, and concluded with field practice. The education was well-received by participants, who engaged actively throughout. A key finding was that while most Putri Sembilan Village residents utilize the mangrove ecosystem for educational ecotourism and to mitigate residential land abrasion, there remains a limited understanding of mangrove forest preservation and silvofishery utilization for mangrove crab (Scylla serrata) cultivation. Post-activity evaluation demonstrated that silvofishery education significantly improved residents' understanding of the balance between utilization and conservation. It is recommended that this educational activity be followed up with practical training and assistance in mangrove crab cultivation for community groups dedicated to preserving the Putri Sembilan Rupat Utara Village ecosystem.